Data work in context: Value, risks, and governance. (19th November 2018) - Foster, Jonathan; McLeod, Julie; Nolin, Jan; Greifeneder, Elke
Abstract : While always integral to scientific activity, data work has recently emerged as a key set of processes within societal activities of all kinds. While data work presents new opportunities for discovery, value creation, and decision making, its emergence also raises significant ethical issues, including those of ownership, privacy, and trust. This article presents a review of data work, and how negotiating a trade‐off between its value and risks requires locating its processes within the contexts of its conditions and consequences. These include international, national, and sectoral conditions of law, policy, and regulation at a macro level; organizational conditions of information and data governance that aim to address the value and risks of data work at a meso level; along with attention to the everyday contexts of data and information handling by data information and other professionals at a micro level. In conclusion, a conceptual framework is presented that locates the processes of data work within the matrix of its macro meso and micro conditions, its consequences for individuals, organizations, and society, and the relations between them. Suggestions are given for how research into the study of data work—its value risks and governance— can be advanced by using this framework.